Is the Korean developmental state a model to follow? - Pęciak, Renata (Czy koreański model państwa rozwojowego jest wzorem do naśladowania?, 2018)
Dynamic industrialisation process that started in the 1960s changed South Korea from poor and underdeveloped economy into one of the largest economic and export powers with high GDP per capita. The developmental state was the fundamental determinant of success and spiritus movens of modernisation process. While taking enforcement measures, repressions against workers and society, as well as strong interventions in industry, farming and financial sector, the visible hand of state targeted the development and implemented ambitious economic goals. The policy affected the contemporary economy of South Korea. The goal of the paper is to explain the essence of Asian developmental state, show the most important actions implemented by Korean developmental state as well as disputes arising from these actions in the period of modernisation and the impact of these actions on contemporary socio-economic system in Korea
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 312-323
Keywords: developmental state; South Korea; model of East Asia growth; Park Chung-hee regime; państwo rozwojowe; Korea Południowa; wschodnioazjatycki model wzrostu gospodarczego; reżim Park Chung-hee